Matrix Metalloproteinases MMP-2 and MMP-9 Occupy a New Role in Severe Preeclampsia - Elena Timokhina; Alexander Strizhakov; Sapiyat Ibragimova; Evgeny Gitel; Irina Ignatko; Vera Belousova; Nikoleta Zafiridi (Hindawi Limited, 2020)
Introduction. Preeclampsia (PE) is a life-threatening condition for the mother, the fetus, and the newborn. Matrix metalloproteinases (MMP) participate in the two primary stages of PE: remodeling of blood vessels at the stage of placental formation and the development of hypertension due to damage to the basement membrane of blood vessels. The object of the present study was to reveal the role of MMP-2 and MMP-9 in the development of severe preeclampsia. Materials and Methods. We conducted a retrospective study that included 92 pregnant women at a gestational age of 26-38 weeks, of which the principal group consisted of 61 patients with severe PE. We divided the principal group into two subgroups: the first subgroup was designated the severe early-onset preeclampsia (EO-PE) group and consisted of 30 pregnant women. The second group was designated the severe late-onset preeclampsia (LO-PE) group, comprising 31 patients. We determined the plasma concentrations of MMPs 2 and 9 in the groups with an ELISA. Results. In the group of PE patients with both EO-PE and LO-PE, the level of MMP-2 was significantly higher compared to the women undergoing normal pregnancy; and we observed no significant differences when we compared the levels of MMP-2 in the subgroups with EO-PE and LO-PE. Analysis of the concentrations of MMP-9 in EO-PE and LO-PE subgroups revealed attenuated levels of MMP-9 in both groups relative to the control group. We also noted a diminished level of MMP-9 in the EO-PE group compared to the LO-PE group. Conclusions. The significantly increased levels of MMP-2 in women-both in the EO-PE and LO severe PE subgroups-explain the participation of this enzyme in endothelial dysfunction in the second stage of severe PE. A diminution in MMP-9 in the EO-PE group confirmed the participation of MMP-9 in the process of spiral artery transformation.